2013
DOI: 10.3389/fpsyt.2013.00145
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy in Schizophrenia: A Possible Biomarker for Predicting Clinical Outcome and Treatment Response

Abstract: Functional near-infrared spectroscopy (fNIRS) is a relatively new technique that can measure hemoglobin changes in brain tissues, and its use in psychiatry has been progressing rapidly. Although it has several disadvantages (e.g., relatively low spatial resolution and the possibility of shallow coverage in the depth of brain regions) compared with other functional neuroimaging techniques (e.g., functional magnetic resonance imaging and positron emission tomography), fNIRS may be a candidate instrument for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 103 publications
(166 reference statements)
4
71
2
Order By: Relevance
“…Second, although we have previously reported and reviewed other studies that have shown that medication has little influence on brain activity as measured by NIRS in larger sample sizes (Koike et al, 2013a), the present study showed a significant correlation between the NIRS signal and chlorpromazine equivalent dose. This correlation was found irrespective of the genotype; however, we conducted a confirmation analysis to exclude the potential effects of medication using ANCOVA, and we found no effect of medication on the results.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Second, although we have previously reported and reviewed other studies that have shown that medication has little influence on brain activity as measured by NIRS in larger sample sizes (Koike et al, 2013a), the present study showed a significant correlation between the NIRS signal and chlorpromazine equivalent dose. This correlation was found irrespective of the genotype; however, we conducted a confirmation analysis to exclude the potential effects of medication using ANCOVA, and we found no effect of medication on the results.…”
Section: Discussioncontrasting
confidence: 75%
“…This correlation was found irrespective of the genotype; however, we conducted a confirmation analysis to exclude the potential effects of medication using ANCOVA, and we found no effect of medication on the results. Antipsychotics are not thought to act on glutamate receptors directly and there has been no study to find any effect of antipsychotics medication on brain activity measured by NIRS in patients with schizophrenia (Koike et al, 2013a), but potential gene × medication interactions should be considered (Bishop et al, 2005;Marumo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prefrontal activity markers during chewing and somatic state examinations, such as SCL-90-R, may be useful in clinical settings to analyze the neuro-pathological background in patients complaining of persistent OD. This suggestion is in line with previous research results showing that fNIRS is a functional imaging method that relies on the principal of neurovascular couplings and applicable for evaluation of psychiatric state using prefrontal cortex blood flow in patients with psychiatric disorders [22,23,[58][59][60][61][62][63].…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that frontal hemodynamic patterns measured by NIRS can be a biomarker for the diagnosis of schizophrenia 1,2) . However, some researchers have stated that findings detected with NIRS may not be trait markers but state markers 3,4) . Therefore, in the present case, we measured NIRS a total of four times during the clinical course of the acute phase of a patient with first -episode schizophrenia.…”
Section: Introductionmentioning
confidence: 99%